Functional difficulties and school limitations of children with epilepsy: Findings from the 2009–2010 National Survey of Children with Special Health Care Needs. Issue 2 (April 2015) - Pastor, Patricia N.; Reuben, Cynthia A.; Kobau, Rosemarie; Helmers, Sandra L.; Lukacs, Susan
Abstract: Background: Epilepsy is a common serious neurologic disorder in children. However, most studies of children's functional difficulties and school limitations have used samples from tertiary care or other clinical settings. Objective: To compare functional difficulties and school limitations of a national sample of US children with special health care needs (CSHCN) with and without epilepsy. Methods: Data from the 2009–2010 National Survey of CSHCN for 31, 897 children aged 6–17 years with and without epilepsy were analyzed for CSHCN in two groups: 1) CSHCN with selected comorbid conditions (intellectual disability, cerebral palsy, autism, or traumatic brain injury) and 2) CSHCN without these conditions. Functional difficulties and school limitations, adjusted for the effect of sociodemographic characteristics, were examined by epilepsy and comorbid conditions. Results: Three percent of CSHCN had epilepsy. Among CSHCN with epilepsy 53% had comorbid conditions. Overall CSHCN with epilepsy, both with and without comorbid conditions, had more functional difficulties than CSHCN without epilepsy. For example, after adjustment for sociodemographic characteristics a higher percentage of children with epilepsy, compared to children without epilepsy, had difficulty with communication (with conditions: 53% vs. 37%, without conditions: 13% vs. 5%). Results for school limitations were similar. After adjustment, a higher percentage of children with epilepsy, compared to children without epilepsy, missed 11 + school days in the past year (with conditions: 36% vs. 18%, without conditions: 21% vs. 15%). Conclusion: CSHCN with epilepsy, compared to CSHCN without epilepsy, were more likely to have functional difficulties and limitations in school attendance regardless of comorbid conditions.